MEDICINAL PLANTS USED IN TRADITIONAL HERBAL MEDICINE IN THE PROVINCE OF CHIMBORAZO, ECUADOR. - Morales, Fatima; Padilla, Susana; FalconÃ, Félix (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Phyto-therapy studies on Chimborazo province in Ecuador are really limited. This area, located within theAndes, is considered a millenarian and intercultural province, where multiples cultures and ethnic groups coexist.Materials and Methods: The study was conducted through direct interviews with 84 ancestral healers from the Province ofChimborazo, Ecuador.Results: We presented ten most used species by ancestral healers of Chimborazo province to cure different illnesses andtheir medicinal uses. We also provided the application mode and some features of healing that should be emphasized.Conclusion: The nettle was the medicinal plant employed for more different illness and the chamomile was the one withhigher prevalence. We could confirm that the Native Ecuadorians have a vast variety of traditions and popular medicinalpractices that have great value and are needed to be researched and studied extensively.